2012
DOI: 10.1021/mp300529a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Capacity of Low Glass Transition Temperature Excipients to Minimize Amorphization of Sulfadimidine on Comilling

Abstract: The co-processing of active pharmaceutical ingredient (API) with an excipient which has a high glass transition temperature (Tg) is a recognised strategy to stabilise the amorphous form of a drug. This work investigates whether co-processing a model API, sulfadimidine (SDM) with a series of low Tg excipients prevents or reduces amorphisation of the crystalline drug. It was hypothesised that these excipients could exert a Tg lowering effect, resulting in composite Tg values lower than that of the API alone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Co-milling and freeze drying with hydrophilic polymers were used to form amorphous glass solutions and hot-melt extrusion of drugs using mixtures of low-melting polymers and surfactants were also employed for co-amorphization (Zhang et al, 2014). Some di and tricarboxylic acids have the ability to adjust the glass transition temperature of the composite solid dispersion by the antiplasticizing effects thus protecting the amorphous state of the resulting dispersion (Curtin et al, 2012). In this study, solvent evaporation under vacuum was used for the preparation of solid dispersions of OL and poly carboxylic acids followed by incorporation of successful co-amorphous dispersions into different film formulations, followed by incorporation in different film formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Co-milling and freeze drying with hydrophilic polymers were used to form amorphous glass solutions and hot-melt extrusion of drugs using mixtures of low-melting polymers and surfactants were also employed for co-amorphization (Zhang et al, 2014). Some di and tricarboxylic acids have the ability to adjust the glass transition temperature of the composite solid dispersion by the antiplasticizing effects thus protecting the amorphous state of the resulting dispersion (Curtin et al, 2012). In this study, solvent evaporation under vacuum was used for the preparation of solid dispersions of OL and poly carboxylic acids followed by incorporation of successful co-amorphous dispersions into different film formulations, followed by incorporation in different film formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Particle engineering and solid form modification of APIs and functional excipients can occur during spray drying [66,67], crystallization [68], milling [69,70], wet extrusion, wet granulation and hot melt extrusion [71]. Multiparticulate systems and tablet dosage forms can be coated by functional excipients to modify drug release [72], to avoid chemical degradation [73] and to reduce irritation of parts of the gastrointestinal tract [74].…”
Section: Phase Transformation Of Hydrates and Solvatesmentioning
confidence: 99%
“…Without an obvious sign of recrystallization, the diacids with relatively low T g s, i.e., MAE (4.6 • C) and MAL (−20 • C), on the other hand, resulted in Class III GFA behavior [16,40]. It has been shown that for co-milling and spray-drying, which are also major sources of inducing amorphization, high T g excipients confer functional advantages for stabilizing the amorphous drugs [41][42][43][44][45]. However, the opposite trend was observed in our study, i.e., the crystallization tendency was positively correlated with the T g of the coformer (Figure 2).…”
Section: Role Of C4 Diacid Coformers In Altering the Glass-forming Abmentioning
confidence: 99%